Secretion of IFN-γ by Transgenic Mammary Epithelial Cells in vitro Reduced Mastitis Infection Risk in Goats - Liu, Ying; Zhang, Hongyan; Dong, Shasha; Li, Boyu; Ma, Weiming; Ge, Lijiang; Hu, Zhiyong; Su, Feng (Frontiers in Veterinary Science, 2022)
Mastitis results in great economic loss to the dairy goat industry. Many approaches have attempted to decrease the morbidity associated with this disease, and among these, transgenic strategy have been recognized as a potential approach. A previous mammalian study reports that interferon-gamma (IFN-γ) has potential anti-bacterial bioactivity against infection in vitro; however, its capacity in vivo is ambiguous. In this study, we initially constructed targeting and homologous recombination vectors (containing the IFN-γ gene) and then transferred the vectors into goat mammary gland epithelial cells (GMECs). Enzyme digestion and sequencing analysis indicated that the vectors used in this study were built correctly. Subsequently, monoclonal cells were selected using puromycin and the polymerase chain reaction (PCR) test indicated that IFN-γ was correctly inserted downstream of the casein promoter. Monoclonal cells were then assessed for reducible expression, and reverse transcriptase-PCR (RT-PCR) and Western blot tests confirmed that monoclonal cells could express IFN-γ. Finally, anti-bacterial capacity was evaluated using bacterial counts and flow cytometry analysis. Decreased bacterial counts and cell apoptosis rates in transgenic GMECs demonstrated that the secretion of IFN-γ could inhibit bacterial proliferation. Therefore, IFN-γ gene transfection in goat mammary epithelial cells could inhibit bacterial proliferation and reduce the risk of mammary gland infection in goats.